Striving for Balance in Arvydas Šliogeris’ Philosophy - Kučinskas, Justas; Kardelis, Naglis (Problemos, 2015)
The authors of the article argue that Arvydas Šliogeris’ philosophy, although prima facie very radical, is in its essence actually based on the striving for balance as its main intention. It is also argued that the thought of this philosopher revolves around the structures of balance. Looking at how, when and what kind of ontological givens and entities find their particular point of balance between certain polar opposites, helps to better understand the philosophy of Šliogeris as a complex conceptual whole as well as to reveal its deepest motivational grounds. Using the notion of balance as a starting heuristic point, the authors of the article present a novel reconstruction of Šliogeris’ thought. One of the results of this reconstruction is a conclusion that this philosophy might be viewed in terms of two distinct evolutionary stages.